2004
DOI: 10.1023/b:urol.0000034664.39784.33
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of transrectal power Doppler imaging in the detection of prostate cancer

Abstract: To evaluate the clinical usefulness of power Doppler imaging (PDI), we compared this method to gray-scale transrectal ultrasound (TRUS) in the detection of prostate cancer. A total of 101 men with abnormally high serum prostate specific antigen (PSA) levels and/or abnormal digital rectal examination (DRE) findings were assessed using TRUS and PDI. Random systematic sextant and bilateral far lateral prostate biopsies were performed in all cases. In addition, when TRUS revealed a hypoechoic lesion or PDI reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Abnormal findings on MRI and TRUS are also significant predictors of PCa, particularly in the initial biopsy setting (31). By contrast, in the repeat biopsy setting, the present study demonstrated that the incidence of abnormal findings on DRE, TRUS and/or MRI in patients with PCa was not significantly higher than that in patients with no evidence of cancer.…”
Section: Discussionmentioning
confidence: 42%
“…Abnormal findings on MRI and TRUS are also significant predictors of PCa, particularly in the initial biopsy setting (31). By contrast, in the repeat biopsy setting, the present study demonstrated that the incidence of abnormal findings on DRE, TRUS and/or MRI in patients with PCa was not significantly higher than that in patients with no evidence of cancer.…”
Section: Discussionmentioning
confidence: 42%
“…Serum markers, such as p53 antibody and insulin‐like growth factor 1 (IGF‐1), have also been examined to improve positive predictive value 10,11 . Furthermore, advances in PCa visualization such as magnetic resonance spectroscopic imaging, dynamic contrast‐enhanced magnetic resonance imaging, positron emission tomography and transrectal power Doppler imaging have improved the positive predictive value 12,13 . Because prostate biopsy can be a painful procedure with potentially significant morbidity, a valid management goal must therefore be to minimize the rate of negative biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 40% of the peripheral zone hypoechoic lesions prove malignant (Shinohara et al 1989). Furthermore, isoechoic and even hyperechoic tumors have been ob- served (Inahara 2004). Therefore, the clinical value of TRUS is limited to a biopsy guidance tool.…”
Section: State-of-the-art In Image-based Computer-aided Diagnosis Of mentioning
confidence: 99%